2015
DOI: 10.1063/1.4921111
|View full text |Cite
|
Sign up to set email alerts
|

Refining the phase diagram of Pb1−xLax(Zr0.9Ti0.1)1−x/4O3 ceramics by structural, dielectric, and anelastic spectroscopy investigations

Abstract: We present the results of dielectric and anelastic spectroscopy measurements, together with X-ray diffraction investigations, which allow us to establish more precisely the phase diagram of Pb1−xLax(Zr0.9Ti0.1)1−x/4O3 (PLZT x/90/10) in the compositional range around the AFE/FE phase boundary (0 < x < 0.04). From structural analysis and polarization-electric field measurements, we have found that the ground state of PLZT samples with x < 0.025 is rhombohedral R3c, while samples with x &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…Despite earlier discovery of the AFE/FE phase boundary in Pb 1− x La x (Zr 0.9 Ti 0.1 ) 1− x /4 O 3 (PLZT x /90/10), the energy storage properties across the border have not been adequately addressed . By replacing La 3+ (from 2 to 4 at.%) for A‐site perovskite PLZT x /90/10 ferroelectric material, the properties of ferroelectrics PLZT x /90/10 can be modified, and the AFE orthorhombic phase gradually increases at the expenses of the FE rhombohedral one, whereas PLZT x /90/10 undergoes a FE rhombohedral and AFE orthorhombic transformation . A coexistence of AFE and FE phases in PLZT x /90/10 ceramics with La compositions close to FE to AFE boundary has been previously reported .…”
Section: Introductionmentioning
confidence: 99%
“…Despite earlier discovery of the AFE/FE phase boundary in Pb 1− x La x (Zr 0.9 Ti 0.1 ) 1− x /4 O 3 (PLZT x /90/10), the energy storage properties across the border have not been adequately addressed . By replacing La 3+ (from 2 to 4 at.%) for A‐site perovskite PLZT x /90/10 ferroelectric material, the properties of ferroelectrics PLZT x /90/10 can be modified, and the AFE orthorhombic phase gradually increases at the expenses of the FE rhombohedral one, whereas PLZT x /90/10 undergoes a FE rhombohedral and AFE orthorhombic transformation . A coexistence of AFE and FE phases in PLZT x /90/10 ceramics with La compositions close to FE to AFE boundary has been previously reported .…”
Section: Introductionmentioning
confidence: 99%
“…[24][25] Since the Pbam ground state is close in energy to a rhombohedral R3c phase, 33 The initially single 200pc reflection develops a distinct shoulder on the lower 2 side (Fig. 2(d)).…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] The AFE-to-FE phase transition is a complex phenomenon, which includes structural phase transformations, unit cell volume changes, domain switching and texture formation. 5,[13][14][15][16][18][19][20][21][22] The AFE-to-FE transition has been reported using macroscopic studies, 12,[23][24][25] however microscopic studies to date are scarce. 5,[13][14][15][16][18][19][20][21][22] There is much that can be learned from studying the structural evolution at various fields before, during and after the AFE-to-FE phase transition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This composition, which is in a ferroelectric state at room temperature under atmospheric pressure, can be transformed into the antiferroelectric phase by the application of a hydrostatic pressure or by increasing the temperature [11]. More recently, a new phase diagram has been established for PLZT x/90/10 [12]. It has been reported that below 0.025 at% of lanthanum, there is a FE phase; above 0.032 at% there is an AFE phase; and for 0.025<x<0.032, a coexistence of the AFE/FE phases is evidenced.…”
Section: Introductionmentioning
confidence: 98%